THE INFLUENCE OF BRANDING AND IMAGE ON CUSTOMER SATISFACTION AT YOGS BARBERSHOP IN MALANGO' RANTEPAO DISTRICT, NORTH TORAJA DISTRICT - Jen, Jen; Limbongan , Enggane; Ronal , Marinus (JURNAL EKBIS, 2025)
This research aims to determine: (1) the influence of branding on customer satisfaction of Yogs Barbershop in Malango', (2) the influence of image on customer satisfaction of Yogs Barbershop in Malango', (3) the influence of branding and image on customer satisfaction of Yogs Barbershop in Malango'. The research results show that: (1) there is a positive influence of branding on customer satisfaction at Yogs Barbershop in Malango', as evidenced by a calculated t value of 2.996; significance value 0.004 < 0.05; and the regression coefficient is 0.326; (2) there is a positive influence of image on customer satisfaction at Yogs Barbershop in Malango', as evidenced by the calculated t value of 3.538; significance value 0.001 < 0.05; and the regression coefficient is 0.382; and (3) there is an influence of branding and image together on customer satisfaction at Yogs Barbershop in Malango', as evidenced by the calculated F value of 60.666 and a significance of 0.000<0.05.